PENEGAKAN HUKUM TERHADAP PERAN ARTIFICIAL INTELLIGENCE DI INDONESIA PENEGAKAN HUKUM TERHADAP PERAN ARTIFICIAL INTELLIGENCE DI INDONESIA - Annie Long Ashton; Anak Agung Sagung Laksmi Dewi; I Gusti Agung Ayu Gita Pritayanti Dinar (Jurnal Analogi Hukum, 2024)
The development of information and digital technology is accelerating and has become part of every aspect of human life. Humans have made innovations in various fields, including machines and technologies that mimic human intelligence known as artificial intelligenceartificial intelligence or AI. The problem is: How can Artificial IntelligenceArtificial intelligence arrangements be considered capable as legal subjects? And how is proper law enforcement for artificial intelligenceartificial intelligence functions? The purpose of this study is To meet the needs of regulations and information regarding artificial intelligenceartificial intelligence, it is important to establish a legal entity and special provisions. In addition, it is important to determine appropriate law enforcement and make special provisions for the functioning of AI. The method used in this research is the normative method. Artificial IntelligenceArtificial intelligence (AI) is an electronic system that handles electronic information and is managed by electronic agents and operators. However, AI is currently unable to take legal action or mediate. Individuals who control or use AI are responsible for their actions. In Indonesia, AI regulations should emphasize ethics and human rights in control and protection. While there are already laws regarding AI as electronic agents, specific regulations are needed that outline its role, capabilities, limitations on use, and penalties.